Impact of Hemoglobin, Leucocyte and Thrombocyte Levels at Diagnosis on the Survival Outcomes of Chronic Myeloid Leukemia Patients - Taha Ulutan Kars; Atakan Tekinalp; Rafiye Ciftciler; Sinan Demircioğlu (Genel Tıp Dergisi)
Background:Since the development of tyrosine kinase inhibitors (TKIs), the prognosis for chronic myeloid leukemia (CML) has significantly improved. Several predicted prognostic scores and indicators at diagnosis have been used to predict the prognosis of chronic phase chronic myeloid leukemia (CML-CP) during the TKI period. When CML patients are first diagnosed, hemogram parameter aberrations are rather prevalent in clinical practice, although it is still unknown how those parameters affect the prognosis. This study aims to evaluate the hemogram parameters at diagnosis on the survival outcomes of CML-CP patients. Materials and Methods:One hundred thirty-seven patients who were diagnosed with CML-CP and received treatment were assessed between the years 2006 and 2020. Results:There were 65 (47.4%) males and 72 (52.6%) females with a median age of 50 (range: 18-78) years at diagnosis. Median hemoglobin level was 12.1 gr/dL (4.3-17.4), leucocyte count was 66.2 ×109 /L (7.5-520.2), and thrombocyte count was 362 ×109 /L (18-3.496) for all patients. The median progression-free survival (PFS) was 16.7 months 16.7 (2.0-106.4) and the median overall survival (OS) was 63.8 months (0.43-166.2) for all patients. Conclusion:This study is valuable in terms of predicting the prognosis of CML patients with hemoglobin, leukocyte, and platelet values at the time of diagnosis. While emphasizing the importance of platelet count at the time of diagnosis, similar to the previously defined risk scores, it showed that leukocyte and hemoglobin values at the time of diagnosis did not have a statistically significant effect on OS and PFS.